Location and characterization of two widely separated glucocorticoid response elements in the phosphoenolpyruvate carboxykinase gene. - Petersen, D D (1988)
Chimeric genes were constructed by fusion of various regions of the 5'-flanking sequence from the phosphoenolpyruvate carboxykinase (GTP) (PEPCK) gene to the chloramphenicol acetyltransferase-coding sequence and to simian virus 40 splice and polyadenylation sequences. These were used to demonstrate that two glucocorticoid regulatory elements (GREs) combine to confer glucocorticoid responsiveness upon the PEPCK gene in H4IIE hepatoma cells. Both elements, a distal one whose 5' boundary is located between -1264 and -1111 base pairs and a proximal one located between -468 and -420 base pairs relative to the transcription initiation site, act independently, in various positions and orientations, and upon the heterologous thymidine kinase promoter. Each element accounts for half of the maximal response of the chimeric genes. Therefore, two widely separated enhancerlike elements contribute equally to the response of the PEPCK gene to glucocorticoid hormones. Neither of the PEPCK GREs contains the TGTTCT consensus sequence associated with most other GREs.